Resistance to fluoroquinolones and second-line injectable drugs: impact on multidrug-resistant TB outcomes - Falzon, Dennis; Gandhi, Neel; Migliori, Giovanni B; Sotgiu, Giovanni; Cox, Helen S; Holtz, Timothy H; Hollm-Delgado, Maria-Graciela; Keshavjee, Salmaan; DeRiemer, Kathryn; Centis, Rosella; D'Ambrosio, Lia; Lange, Christoph G; et al. (The European respiratory journal, 2013)
A meta-analysis for response to treatment was undertaken using individual data of multidrug-resistant tuberculosis (MDR-TB) (resistance to isoniazid and rifampicin) patients from 26 centres. The analysis assessed the impact of additional resistance to fluoroquinolones and/or second-line injectable drugs on treatment outcome. Compared with treatment failure, relapse and death, treatment success was higher in MDR-TB patients infected with strains without additional resistance (n=4763; 64%, 95% CI 57-72%) or with resistance to second-line injectable drugs only (n=1130; 56%, 95% CI 45-66%), than in those having resistance to fluoroquinolones alone (n=426; 48%, 95% CI 36-60%) or to fluoroquinolones plus second-line injectable drugs (extensively drug resistant (XDR)-TB) (n=405; 40%, 95% CI 27-53%). In XDR-TB patients, treatment success was highest if at least six drugs were used in the intensive phase (adjusted OR 4.9, 95% CI 1.4-16.6; reference fewer than three drugs) and four in the continuation phase (OR 6.1, 95% CI 1.4-26.3). The odds of success in XDR-TB patients was maximised when the intensive phase reached 6.6-9.0 months duration and the total duration of treatment 20.1-25.0 months. In XDR-TB patients, regimens containing more drugs than those recommended in MDR-TB but given for a similar duration were associated with the highest odds of success. All data were from observational studies and methodologies varied between centres, therefore, the bias may be substantial. Better quality evidence is needed to optimise regimens.